Toxic metal (Cd, Hg, Mn, Pb) partition in the maternal/foetal unit: A systematic mini — review of recent epidemiological studies. (10th October 2020) - Kabamba, M.; Tuakuila, J.
Highlights: Partition of toxic metal (Cd, Hg, Mn, Pb) levels in the maternal/foetal unit. Correlation of toxic metal (Cd, Hg, Mn, Pb) levels in the maternal/foetal unit. Cord/maternal ratio of toxic metals (Cd, Hg, Mn, Pb). Proportion of toxic metals (Cd, Hg, Mn, Pb) in cord blood. Hg and Pb levels in maternal blood as predictors for cord levels. Abstract: The aim of this study was to summarise the available information regarding the partition of toxic metal (Cd, Hg, Mn, Pb) levels in the maternal/foetal unit from large epidemiological studies. We performed a systematic search of PubMed/MedLine, EMBASE, and ISI Web of Science for papers on Cd, total Hg, Mn or Pb levels in the maternal/cord blood that were published in English (n > = 200; 2010–2017). Data on year of publication, sample size, location, year of survey, and main results were extracted. We found a total of 35 papers. Most studies included large convenience samples of healthy pregnant women. The maternal/cord blood was properly used as a biomarker of prenatal exposure to toxic metals. The partition of these toxic metal levels in the maternal/foetal unit was metal-specific. Cd median levels (IQR) in cord blood reported worldwide were much lower [∼ 70 % < LOD = ± 0.11 μg/L] than those found in maternal blood [0.23 μg/L (0.15−0.35), ∼ 65 % > LOD]. Considering that Cd was under LOD in 70 % of the cord blood, Cd cord:maternal ratio as well as Cd cord proportion were not provided. Total Hg median levels (IQR) in cord blood [0.75 μg/L (0.40–1.19), ∼30 % < LOD = ±0.35 μg/L] were usually higher than in maternal blood [0.55 μg/L (0.40−0.85), ∼ 10 % < LOD = ±0.15 μg/L]. Hg cord:maternal ratio was 1.34 (1.00–1.91), and infants born would have Hg cord:(cord + maternal) proportion ranged from 0.50 to 0.63. Mn was the only metal that was detected in 100 % in both maternal (LOD : ±0.50 μg/L) and cord (LOD = ±0.2 μg/L) blood. Mn median levels (IQR) in cord blood [32.96 μg/L (26.90–40.10)] were 2 times higher than in maternal blood [14.01 μg/L (11.50–17.58)]. Mn cord:maternal ratio was 2.35 (1.09–3.80), and infants born would have Mn proportion ranged from 0.52 to 0.79. Pb median levels (IQR) in cord blood [5.79 μg/L (4.34–8.38), ∼ 5% < LOD : ±2.07 μg/L] were usually equal to or lower than those reported in maternal blood [8.07 μg/L (5.79–10.76), ∼ 1% < LOD = ±1.03 μg/L]. Pb cord:maternal ratio was 0.71 (0.59−0.96), and infants born would have Pb proportion ranged from 0.37 to 0.49. Globally, the results indicate that total Hg and Mn levels were lower in maternal blood but higher in cord blood. However, much greater variability was seen with Cd and Pb. At delivery, total Hg and Pb levels in maternal blood were strong predictors of cord blood levels. Our findings empty that understanding the partition, levels and correlations of toxic metals in the maternal/cord blood may help to elucidate the adverse effects of these metals on foetuses and neonates.